1987
DOI: 10.1136/pgmj.63.738.303
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy caused by mercury-containing skin lightening cream

Abstract: Summary:A 46 year old woman developed membranous nephropathy following the use of a mercurycontaining skin lightening cream. This association has not been reported in the literature for over a decade and apparently never from this country. It is important that clinicians are aware of this usually eminently treatable cause of the nephrotic syndrome as it is likely to be missed unless specifically enquired for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 7 publications
(1 reference statement)
0
33
0
Order By: Relevance
“…Thus, four deaths and up to 800 people were injured, after using weight-loss supplements containing hidden quantities of the untested drug n-nitroso-fenfl uramine (Lau, 2004). Skin-lightening creams containing mercury were responsible for hundreds of poisoning cases (Oliveira, Foster, Savill, Syme & Taylor, 1987), with creams containing hydroquinone and corticosteroids also causing many harms (Fraser et al, 2010 Note. 1 A number of human enhancement drugs are also legitimate medicines, which have been tested and approved at appropriate dosages for specific conditions.…”
Section: The Harms Associated With Human Enhancement Drugsmentioning
confidence: 99%
“…Thus, four deaths and up to 800 people were injured, after using weight-loss supplements containing hidden quantities of the untested drug n-nitroso-fenfl uramine (Lau, 2004). Skin-lightening creams containing mercury were responsible for hundreds of poisoning cases (Oliveira, Foster, Savill, Syme & Taylor, 1987), with creams containing hydroquinone and corticosteroids also causing many harms (Fraser et al, 2010 Note. 1 A number of human enhancement drugs are also legitimate medicines, which have been tested and approved at appropriate dosages for specific conditions.…”
Section: The Harms Associated With Human Enhancement Drugsmentioning
confidence: 99%
“…Additional cases of membranous GN due to mercury-containing cosmetics have been described by Lindqvist et al [213], Kibukamusoke et al [214]. and Oliveira et al [215], It was later shown by Barr [216] that about 50% of patients in Kenya with nephrotic syndrome suffered from immune-mediated glo merulopathy. All o f them had used skin-lightening cream containing mercury chloride, and an association to HLA phenotype was suggested.…”
Section: Type Hi Hypersensitivity (Immune Complex Mediated)mentioning
confidence: 99%
“…Mercury is absorbed through the skin [12,34,35] and accumulated in different body tissues where the highest is in the kidney [36]. Nephrotoxic effects have been attributed to the topical application of inorganic mercury salts [34,[37][38][39][40][41][42][43][44]. On the other hand, Sin and Tsang [45] found that the majority of skin lightening users had urinary mercury >20 µg/L or blood mercury concentrations >10 µg/L but remained asymptomatic.…”
Section: Introductionmentioning
confidence: 99%